2021
DOI: 10.3389/fpsyg.2021.712582
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Generalization Study of the Person-Centered Care Assessment Tool

Abstract: The so-called Person-Centered Care (PCC) model identifies three fundamental principles: changing the focus of attention from the disease to the person, individualizing care, and promoting empowerment. The Person-Centered Care Assessment Tool (P-CAT) has gained wide acceptance as a measure of PCC in recent years due to its brevity and simplicity, as well as its ease of application and interpretation. The objective of this study is to carry out a reliability generalization meta-analysis to estimate the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In the original study (n = 220; [13]), the internal consistency of the instrument yielded satisfactory values for the total scale (α = .84) and good test-retest reliability (r = .66) at a one-week interval. A reliability generalization study conducted in 2021 [22], which estimated the internal consistency of the P-CAT and analyzed possible factors that could affect it, recorded that the mean α value for the 25 metaanalysis samples (some of which are part of the validations included in this study) was.81, and it was seen that the only variable that had a statistically signi cant relationship with the reliability coe cient was the mean age of the sample. Regarding internal structure validity, three factors (56% of the total variance) were obtained, as well as content validity estimated by experts, literature reviews and stakeholders [23].…”
Section: Person-centered Care (Pcc)mentioning
confidence: 87%
See 2 more Smart Citations
“…In the original study (n = 220; [13]), the internal consistency of the instrument yielded satisfactory values for the total scale (α = .84) and good test-retest reliability (r = .66) at a one-week interval. A reliability generalization study conducted in 2021 [22], which estimated the internal consistency of the P-CAT and analyzed possible factors that could affect it, recorded that the mean α value for the 25 metaanalysis samples (some of which are part of the validations included in this study) was.81, and it was seen that the only variable that had a statistically signi cant relationship with the reliability coe cient was the mean age of the sample. Regarding internal structure validity, three factors (56% of the total variance) were obtained, as well as content validity estimated by experts, literature reviews and stakeholders [23].…”
Section: Person-centered Care (Pcc)mentioning
confidence: 87%
“…A review of this type is critical given some methodological issues that seem not to have been resolved in the P-CAT; for example, although the multidimensionality of the P-CAT was identi ed in the study that constructed it, Bru-Luna et al [22] recently stated that in adaptations of the P-CAT [16][17][18][19][20]25], the total score was used for interpretation, and multidimensionality was disregarded. Thus, the multidimensionality of the original study was apparently not replicated.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the original study (n = 220; [21]), the internal consistency of the instrument yielded satisfactory values for the total scale (α = 0.84) and good test-retest reliability (r =.66) at one-week intervals. A reliability generalization study conducted in 2021 [32] that estimated the internal consistency of the P-CAT and analyzed possible factors that could affect the it revealed that the mean α value for the 25 meta-analysis samples (some of which were part of the validations included in this study) was 0.81, and the only variable that had a statistically significant relationship with the reliability coefficient was the mean age of the sample. With respect to internal structure validity, three factors (56% of the total variance) were obtained, and content validity was assessed by experts, literature reviews and stakeholders [33].…”
Section: Person-centered Care Assessment Tool (P-cat)mentioning
confidence: 95%
“…A review of this type is critical given that some methodological issues seem to have not been resolved in the P-CAT. For example, although the multidimensionality of the P-CAT was identified in the study that introduced it, Bru-Luna et al [32] recently stated that in adaptations of the P-CAT [25,[27][28][29][30]40], the total score is used for interpretation and multidimensionality is disregarded. Thus, the multidimensionality of the original study was apparently not replicated.…”
Section: Current Studymentioning
confidence: 99%